Thermally tunable selective formation of self-assembled fibers into two orthogonal directions in oriented liquid-crystalline smectic templates. Issue 69 (17th July 2020) - Yamaguchi, Daisuke; Ikemoto, Yuka; Kato, Takashi
Abstract : Two orthogonal (grid-like) and one directional fibrous structures are selectively formed through anisotropic self-assembly of low-molecular-weight gelators in liquid-crystalline smectic A templates depending on thermally tuned layered structures. Abstract : We demonstrate the formation of grid-type (crossed perpendicular to each other) fibrous assemblies of low-molecular-weight gelators in aligned liquid-crystalline smectic templates. In the template of layered structures, a gelator forms oriented fibers with one directional and two orthogonal directional (grid-like) alignment depending on the order of layered structures.